Analysis of the Effect of Leisure Sports on the Psychological Anxiety Intervention of Civil Litigation Participants - Kaisi Zheng, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The aim of this study was to examine the relationship between recreational sports and psychological anxiety among participants in civil litigation. 630 men and 648 women from a variety of occupations and educational levels made up the sample, which was broken down into four age categories (20–30, 31–40, 41–50, and above 50). The SCL-90 and other standardized tools were used to measure psychological anxiety. The frequency, length, and preferences for various leisure sports activities were also assessed using a questionnaire. The findings revealed that participants in civil litigation had an average psychological anxiety score of 1.50, which was on the high side of normal but within range. Younger individuals had greater levels of psychological anxiety, according to a single component analysis of psychological anxiety across age groups. A robust inverse relationship between scores in recreational sports and the three aspects of psychological anxiety was established by correlation analysis. Moreover, multiple comparisons demonstrated significant differences in psychological anxiety levels among various levels of leisure exercise. Regression analysis revealed that leisure preference, frequency, and duration of activities significantly predicted psychological anxiety. These factors accounted for 73.7% of the variation in psychological anxiety, with leisure preference alone explaining 34.7% of the variation. Along with these findings, this research contributed to a deeper understanding of the relationship between leisure sports and psychological anxiety among civil litigation participants, suggesting the incorporation of leisure sports programs in mental health interventions for this population.